Countering Marginalisation: A Collaborative Governance Model for Regu-lating Indigenous Peoples’ Land Rights Based on Local Wisdom - Iwan Permadi; Diah Pawestri Maharani; Ashabul Kahfi Ly Aby; Rina Yulianti; Cuikitalia Cuikitalia; Pipit Tunjungsari (Faculty of Law, Sriwijaya University, Indonesia, 2026)
Before Indonesian independence, Mandar people in Mamuju Regency used kumah (shifting farming) to obtain land. Customary domains overlap with protected forest areas encompassing 60–70% of the regency, and their land rights are unrecognised. The 2025–2045 Mamuju RPJPD designates ancestral lands, including Rimuku, Tadui, and Bambu, as strategic zones for the region's Nusantara Capital support city, worsening the issue. This paper examines the legal status of customary land in these vital zones, explains how land-rights neglect marginalises the Mandar people, and proposes a collaborative governance approach grounded in Mandar local wisdom to preserve their land rights. The socio-legal approach that combines normative analysis of land regulations with empirical data from Focus Group Discussions and questionnaires with academics, the National Land Agency (BPN), and the Mandar community finds that marginalisation occurs systematically through three mechanisms: stagnant implementation of regional regulations in customary-law communities without a Regent's response. The study recommends a collaborative governance model that integrates Mandar values of sipakatau (mutual humanisation), sipakalebbi (mutual respect), sisallang (deliberation for consensus), and sipakaingge (mutual reminding) with accelerated recognition of customary land rights.